(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We will present in this article the little corpus of stamps found during the archaeological excavation of the Mas de Moreno kiln (Foz- Calanda, Teruel, IInd-Ist c. B.C.). This corpus can be linked with a precise archaeological context and allows to cross data with other aragoneses Iberian sites. It also allows a deep reflection about the indigenous production structure and its changes under roman influence.